A IMPLEMENTASI PEMBELAJARAN TERINTEGRASI MODEL SHARED DI SEKOLAH DASAR - Devi Ristyana Puji Lestar; Suryanti; Neni Mariana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the implementation of the shared learning model in learning about cultural diversity in Indonesia in elementary schools. The shared model integrates two overlapping scientific disciplines. In this research, integration in the subjects of fine arts and Pancasila education is used with overlapping concepts, namely regarding cultural diversity in Indonesia. This research uses a qualitative approach to obtain descriptive data. Data was collected through classroom observations, documentation, and interviews. The research results show that students' perceptions of shared learning models are generally positive. Students feel learning is more interesting and relevant because it is directly related to their daily lives. Students also gain a deeper understanding of Indonesia's cultural diversity, students learn to respect other cultures, and improve their social skills and ability to work together in teams. The implementation of the shared model allows the integration of knowledge from two subjects, such as fine arts and Pancasila education. This learning encourages active student involvement through practical activities such as working on worksheets, making drawings, and class exhibitions. Students become more aware of cultural diversity in Indonesia and learn the values ​​of tolerance and mutual respect. This research concludes that the shared learning model is effective in improving the quality of education and students' understanding of cultural diversity, and is worthy of widespread application to achieve holistic and inclusive learning goals.